The development of E-BISA media to improve srudents creativity in learning dance in grade VI - Setyaningrum, Riska; Ary, Deasylina da (Jurnal Prima Edukasia, 2026)
This study aims to develop E-BISA media (interactive audiovisual-based ebook) and test its feasibility and effectiveness in increasing student creativity in dance learning for grade VI elementary school. The type of research applied is R&D (Research and Development) with the Borg & Gall development model with seven stages, namely potential and problems, data collection, product design, product validation, revision, trial, and final product. The subjects in this study consisted of grade VI students of Sadeng 02 Public Elementary School, class teachers, as well as material experts and media experts. Data collection techniques used observation, interviews, questionnaires, and documentation. The results of the development of this E-BISA media include interactive audiovisual-based ebook learning media in digital form equipped with images, audio, mystery cards and containing stories with traditional game themes to help students understand the material in dance learning. The results of the feasibility measurement show that the developed E-BISA media has a very high level of feasibility, indicated by the percentage of validation from material experts of 95.7% and media experts of 96%. Furthermore, the trial results showed an increase in student creativity, as demonstrated by a significant difference between pretest and posttest scores. The effectiveness test results indicated that the media used was categorized as quite effective with an N-Gain of 68.22%. Therefore, the E-BISA (audiovisual-based interactive ebook) media is deemed feasible and effective for use in dance learning to enhance student creativity. This media can also be an innovative alternative for teachers in creating engaging, interactive, and technologically advanced learning.